Preparation of SiO2 coated Ce2S3 red pigment with improved thermal stability - 陈观宏 朱振峰 刘辉 武英峰 朱春奎 (Journal of rare earths, 2013)
SiO2 coated Ce2S3 red pigment was prepared in ethanol/H2O system via sol-gel method and TEOS were used as silica sources. X-ray diffraction （XRD）, scanning electron microscopy （SEM）, energy dispersive spectroscopy （EDX）, UV-visible spectro-photometer and automatic colorimeter were used to investigate the properties of the samples. The results showed that the compact SiO2 film formed on the surface of Ce2S3 pigment at a cerium silicon molar ratio of 2. The thermal stability temperature of Ce2S3 pigment was improved to 450 oC after SiO2 coating. In addition, the color of Ce2S3 pigment was not affected significantly through coating colorless and transparent SiO2 and it could be used as safe red pigment in higher temperature fields.